General or central government? Empirical evidence on political cycles in budget composition using new data for OECD countries - Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Previous studies used general government data to examine whether national governments' electoral motives and ideology influenced budget composition in OECD countries. General government data includes, however, the state and local level. Using new data for general and central government over the period 1995-2016, I reexamine political cycles in budget composition. The results suggest that, both at the general and central government level, leftwing governments spent more on education and less on public services than rightwing governments. Defense expenditure was somewhat lower under leftwing than rightwing governments and in election years; especially in federal states. Effects of government ideology on the individual expenditure categories are larger at the central than general government level. Scholars need to re-examine results on ideology-induced effects that have been derived from general government data where central government data should have been used.
Keywords: D72; D78; E60; H30; H50; C23; P16; 330; general and central government; budget composition; partisan politics; government ideology; electoral cycles; OECD countries; panel data models